Nursing students motivation toward their studies - a survey study - Nilsson Kerstin EL; Warrén Stomberg Margareta (BMC, 2008)
Abstract Background This study focuses on Swedish nursing students' motivation toward their studies during their three year academic studies. Earlier studies show the importance of motivation for study commitment and result. The aim was to analyze nursing students' estimation of their degree of motivation during different semester during their education and to identify reasons for the degree of motivation. Methods A questionnaire asking for scoring motivation and what influenced the degree of motivation was distributed to students enrolled in a nursing programme. 315 students who studied at different semesters participated. Analyzes were made by statistical calculation and content analysis. Results The mean motivation score over all semesters was 6.3 (ranked between 0-10) and differed significantly during the semesters with a tendency to lower score during the 5th semester. Students (73/315) with motivation score <4 reported explanations such as negative opinion about the organisation of the programme, attitude towards the studies, life situation and degree of difficulty/demand on studies. Students (234/315) with motivation score >6 reported positive opinions to becoming a nurse (125/234), organization of the programme and attitude to the studies. The mean score value for the motivation ranking differed significantly between male (5.8) and female (6.8) students. Conclusion Conclusions to be drawn are that nursing students mainly grade their motivation positive distributed different throughout their entire education. The main motivation factor was becoming a nurse. This study result highlights the need of understanding the students' situation and their need of tutorial support.